Report on the Launch of the "Asia in Malaysia Forum" - Editor, The (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The term "Asia" has been used so frequently since World War II such that it is assumed that it denotes a society that is homogeneous. In reality, "Asia" is only a geographical location which constitutes many nation states with an ethnic population that is neally uncountable in number.